Avaliação da dinâmica lipídica no modelo de demência vascular - Severiano, Dryelle Lohanne dos Reis (2019)
Vascular dementia (DV) is a neurodegenerative disease caused by several factors that impair cerebral blood flow, such as cerebral ischemia, atherosclerosis, or stroke. These factors impair lipid homeostasis in the brain. The understanding of changes in lipid dynamics in DV may reveal biomarkers and new molecular targets for pharmacological intervention. In the present study, the two vessels occlusion model (2VO) was performed to induce the vascular dementia model in Wistar rats and to study the brain lipid dynamics. Initially, memory loss and cognitive ability were observed through the New Object Recognition Task and the Plus-Maze test in 2VO animals when compared to control. The neuronal loss in 2VO animals was confirmed by cresyl violet staining For lipid mapping in brain tissues, we used the imaging technique of Desorption electrospray ionization - Mass Spectrometry (DESI-IMS). The results obtained revealed important lipids altered in the DV model, such as arachidonic acid (AA), docosahexaenoic acid (DHA), decanoic acid and glycerophosphate PA (38: 3). A partial least squares discriminatory analysis (PLS-DA) was able to detect different ions capable of discriminating 2VO animals and control animals. γ-linolenic acid (m/z 277) and stearic acid (m/z 283) had the highest potential for discrimination. The relationship of the data obtained indicates that AA and DHA are associated with the DV process and γ-linolenic acid is the most important variable for group discrimination.